Analisis Kinerja Pegawai pada Dinas Pertanian Kabupaten Karawang - Safitri, Intan Meliyani; Budi Rismayadi; Wike Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the era of organizational dynamics and changing business environments, enhancing employee performance becomes a pivotal factor for the success of an institution. This research aims to investigate and comprehensively analyze the performance of employees in the Department of Agriculture of Karawang Regency. The method in this research is descriptive qualitative. The results of this studyindicate that motivational aspects, such as the fulfillment of physiological needs, security, social relationships, recognition, and self-actualization, have a positive impact on employee performance. A profound understanding of the contributions of employees with initials L, A, and D in achieving quantity targets, maintaining quality, and ensuring timely completion of tasks provides a foundation for designing effective workplace motivation strategies.